Long Branch Church - Grady County Historical Society (Valdosta State University Archives and Special Collection, 2004)
This file concerns Long Branch Church in Grady County, Georgia, and is included in the Churches series within the Grady County Historical Society Collection. Contents encompass newspaper clippings, a church history booklet, and typed letters. The original materials are preserved by the Grady County Historical Society and were provided to Valdosta State University Archives and Special Collections for digitization and online access.
1 PDF, 40 scanned images
Keywords: Grady County (GA.); Church records and registers; Church History; History- Societies, etc.